Peningkatan Pengetahuan Wanita Menopause melalui Pelatihan Kesehatan Sehat dan Bahagia di Masa Menopause - yhenti widjayanti (Jurnal Abdimas Kesehatan (JAK), 2022)
Menopause is a phase of life experienced by every woman. During menopause, there is a decrease in estrogen levels which has an impact of physical changes that cause complaints during menopause which can reduce the quality of life of postmenopausal women. Some menopausal women in Laban Village, Menganti District, Gresik Regency experienced menopausal complaints but they did not know the condition was normal and did not know how to deal with these complaints, so most of them were excessively anxious about the conditions they were experiencing. The purpose of this community service activity is to increase the knowledge of menopausal women through health training activities with the topic of being healthy and happy during menopause. The target of this activity is 21 postmenopausal women and the expected outcome is an increase in knowledge. This community service activity had been held from December 1, 2021 to January 8, 2022. Health training was carried out through individual counseling or group counseling (2-3) people. The media used were leaflets about physical and psychological changes during menopause, physical activity during menopause, and a phytoestrogen diet. The results showed that before health training 57% of menopausal women had less knowledge, after health training 57% had good knowledge. Health training about being healthy and happy during menopause is effective in increasing knowledge. Good knowledge is expected to increase awareness of menopausal women's acceptance of physical and psychological changes that occur during menopause and awareness to overcome menopausal complaints so that quality of life increases.